Outsourcing, information symmetry and governance: The effects of retailers' formal and informal controls on manufacturers' outsourcing performance. Issue 6 (23rd August 2019) - Rosin, Anna Frieda; Stubner, Stephan; Chaurasia, Sushil S.; Verma, Surabhi
Abstract : Purpose: The purpose of this paper is to examine the effects of retailers' organizational controls and controls of their boundary personnel on manufacturers' outsourcing performance. It further assesses the moderating impact of information symmetry in this context. Design/methodology/approach: Data were collected from 230 Indian apparel manufacturers engaged in outsourcing activities with two international retailers. Organizational control is scrutinized as formal and informal controls, and outsourcing performance is studied in terms of efficiency and effectiveness. The partial least squares approach is used to test the proposed research model. Findings: First, the retailers' and the boundary person's formal controls have a direct, positive effect on outsourcing efficiency. Second, although no significant effect of the boundary person's formal controls on outsourcing effectiveness is identified, a significant effect of retailers' formal controls on effectiveness is seen. Third, the boundary person's informal controls are associated with a decrease in efficiency, whereas they have a positive effect on effectiveness. Fourth, although the retailers' informal controls enhance outsourcing effectiveness, they negatively affect efficiency. Fifth, information symmetry is statistically significant in enhancing outsourcing efficiency and effectiveness. Practical implications: The results have important implications for retailers and retailers' boundary persons who are keen to improve their relations with manufacturers. This paper offers practical insights into the ways that manufacturers, boundary personnel and retailers can exercise control mechanisms in order to achieve effective and efficient outsourcing outcomes. Originality/value: The effect of organizational control and information symmetry on outsourcing performance in typical outsourcing practices in manufacturer‒retailer relationships is shown.